Characterization of physicochemical and immunogenic properties of allergenic proteins altered by food processing: a review - Enning Zhou; Qiangqiang Li; Dan Zhu; Gang Chen; Liming Wu (Food Science and Human Wellness)
Food allergens are mainly naturally-occurring proteins with immunoglobulin E (IgE)-binding epitopes. Understanding the structural and immunogenic characteristics of allergenic proteins is essential in assessing whether and how food processing techniques reduce allergenicity. We here discuss the impacts of food processing technologies on the modification of physicochemical, structural, and immunogenic properties of allergenic proteins. Detection techniques for characterizing changes in these properties of food allergens are summarized. Food processing helps to reduce allergenicity by aggregating or denaturing proteins, which masks, modif ies, or destroys antigenic epitopes, whereas, it cannot eliminate allergenicity completely, and sometimes even improves allergenicity by exposing new epitopes. Moreover, most food processing techniques have been tested on purif ied food allergens rather than food products due to potential interference of other food components. We provide guidance for further development of processing operations that can decrease the allergenicity of allergenic food proteins without negatively impacting the nutritional profile.